2012
DOI: 10.1111/j.1439-0531.2012.02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Strain and Parity on the Risk of Litter Loss in Laboratory Mice

Abstract: Pup mortality is a considerable problem in laboratory mouse breeding and the view that parity influence survival of newborn mice is widespread. Some evidence suggests that maternal behaviour is related to offspring mortality in mice. Parental experience is a factor that can improve maternal behaviour and offspring survival in some mammals. However, few papers report a relationship between parity and pup survival in mice. We investigated the influence of strain and parity on loss of entire litters of C57BL/6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 34 publications
5
34
2
1
Order By: Relevance
“…An association of complete litter losses with construction‐related stress supported earlier studies indicating that complete litter losses are rare and likely stemming from a husbandry issue separate from infanticide (Weber et al. 2013a, 2013b). Similarly, the proportion of early deaths (P0–P8) was lower for the quiescent period, 0.15 (47 of 317 born), compared with construction, 0.32 (188 of 587 born).…”
Section: Resultssupporting
confidence: 77%
“…An association of complete litter losses with construction‐related stress supported earlier studies indicating that complete litter losses are rare and likely stemming from a husbandry issue separate from infanticide (Weber et al. 2013a, 2013b). Similarly, the proportion of early deaths (P0–P8) was lower for the quiescent period, 0.15 (47 of 317 born), compared with construction, 0.32 (188 of 587 born).…”
Section: Resultssupporting
confidence: 77%
“…Breeding efficiency is often hampered by problems with reproduction, including pre-weaning pup mortality. In a previous study [2] we found a total mortality rate (calculated as percentage of entire litters being lost before weaning at around 21 days) of 32% for C57BL/6 and 20% for BALB/c, two of the most common strains of laboratory mice. However, reported mortality rates vary greatly; from nearly 0 to 50% in scientific studies of C57BL/6 mice [35] compared to 13% reported by a commercial breeder [6].…”
Section: Introductionmentioning
confidence: 99%
“…Two females of each treatment group destroyed their litters within 4 days of giving birth, and some pup mortality of unknown cause was observed over lactation. Such pup mortality is typical in captive breeding mice (Weber et al ., ) and the change in litter size over lactation did not differ significantly between the groups (Fig. b; Difference between treatments: F 1,19 = 1.04, P = 0.32; interaction between treatment and time: F 9,171 = 0.51, P = 0.57).…”
Section: Resultsmentioning
confidence: 99%